A qualitative study on emotional labor and work-family conflict in caregivers working in nursing homes - Andrade, Cláudia; Costa Neves, Paula (Anales de Psicología / Annals of Psychology, 2023)
Despite evidence suggesting that care work involves the performance of emotional labor an experience of work-family conflict, the relation of these two work experiences remain under-examined. The present study aims to fill this gap by exploring the experiences of performing emotional labor and work-family conflict and their links among caregivers working in nursing homes. To address the research question, we used semi-structured interviews with a sample of 24 female caregivers working full-time in nursing homes in the center and north of Portugal. The results revealed the presence of emotional labor, work-family conflict, and an impact of emotional labor in strain-based work-family conflict. Overall, the results suggested that emotional labor has effects on work-family conflict, pointing to the need that directors of elderly care institutions should consider ways of reducing these harmful effects on workers.